EKSISTENSIALISME SASTRA DALAM LEGENDA DAN TRADISI NUSANTARA DI INDONESIA MELALUI PERSPEKTIF ETNOSEMIODIGITAL - Nensy Megawati Simanjuntak; Zavina Hudaini; Andre Hardianto; Andre Revalino S; Suhartawan Budianto (Aksara: Jurnal Ilmiah Pendidikan Bahasa dan Sastra Indonesia, 2024)
Literature and law are two different fields, but these two fields can be united through a bridge called literature. The presence of literature in the world of knowledge and education brings its own refreshing and color. Through literature, law and literature, researchers can examine customary laws contained in Indonesian legends. This research takes data in the form of four Indonesian legends which are rich in customary law. The data was analyzed through an ethnosemiodigital perspective. Ethnosemiodigital is a combination of three sub-disciplines, namely: ethnography, semiotics and digital. Etnosemiodigital discusses various cultural issues which contain many signs or symbols and sources of information related to this culture can be accessed through spaces or platforms called digital. Data sources in research are words, sentences and paragraphs that exist and represent customary law. This research focuses on explaining forms of customary law that are rich in Indonesian values and culture. This research finds that law and literature, if united, will be rich in values and knowledge. This research also found that customary law in Indonesia shows national identity, national personality and national character, all of which boil down to one word, namely values. Almost all of the Indonesian archipelago's traditions and legends contain values that show the identity and personality of the Indonesian nation. Values are an important aspect in social life to determine the boundaries of norms and the aims and objectives behind an existing culture or custom. Values will work well if the people who live them preserve and cultivate those values themselves.